2020
DOI: 10.1002/hep4.1601
|View full text |Cite
|
Sign up to set email alerts
|

Donor Fecal Microbiota Transplantation Alters Gut Microbiota and Metabolites in Obese Individuals With Steatohepatitis

Abstract: The intestinal microbiota has been linked to the development and prevalence of steatohepatitis in humans. Interestingly, steatohepatitis is significantly lower in individuals taking a plant‐based, low‐animal‐protein diet, which is thought to be mediated by gut microbiota. However, data on causality between these observations in humans is scarce. In this regard, fecal microbiota transplantation (FMT) using healthy donors is safe and is capable of changing microbial composition in human disease. We therefore per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 54 publications
0
75
0
Order By: Relevance
“…Moreover, FMT from obese women with NAFLD to conventional mice fed a chow diet resulted in increased IHTGs within 2 weeks [ 38 ]. It is noteworthy that preliminary FMT studies from human allogeneic vegan donors to NAFLD patients showed inverse results, exhibiting improved necroinflammatory histology and changes in hepatic gene expression involved in inflammation and lipid metabolism [ 39 ].…”
Section: Overview Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FMT from obese women with NAFLD to conventional mice fed a chow diet resulted in increased IHTGs within 2 weeks [ 38 ]. It is noteworthy that preliminary FMT studies from human allogeneic vegan donors to NAFLD patients showed inverse results, exhibiting improved necroinflammatory histology and changes in hepatic gene expression involved in inflammation and lipid metabolism [ 39 ].…”
Section: Overview Of Nafldmentioning
confidence: 99%
“…The FLI was developed and validated to select elderly subjects for ultrasonography to detect NAFLD. The recommended cut-offs are as follows: FLI < 30 to rule out (87% sensitivity) and FLI ≥ 60 to rule in hepatic steatosis (specificity 86%) [ 38 , 39 ]. The NLFS evaluates liver fat content measurements and has shown satisfactory accuracy in diagnosing NAFLD, (95% sensitivity), although in the general population these tools offer lower diagnostic efficacy (70–80%) [ 55 ].…”
Section: Overview Of Nafldmentioning
confidence: 99%
“…The oral use of the antibiotic rifaximin, which is poorly absorbed into the systemic circulation, in patients with liver cirrhosis leads to reduced endotoxemia, modulates the gut microbiome and therefore affects the gut-liver axis [315,316]. FMT proved to be effective in recovering the microbiome and limiting liver inflammation and damage in mice [305,317] and showed reduction of liver disease severity and improved survival after one year in ALD patients [318] and a positive effect on the composition of the microbiome and liver inflammation in patients with NASH [319]. Another important factor influencing microbiome composition which can be used as therapeutic strategy that should not be left unmentioned is nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving manipulation of the microbiome further highlight its important role in regulating body weight. For example, the use of prebiotics and probiotics can reduce body weight and fat mass in obese individuals [ 21 ], and fecal microbiome transplants from healthy donors has been shown to improve glucose metabolism, insulin sensitivity, and liver function in overweight individuals [ 22 , 23 ]. It has also been shown that fecal microbiome transplants from obese individuals promotes weight gain in germ-free, lean rodents despite no change in caloric intake [ 24 , 25 ].…”
Section: Eating Disorders and The Gut Microbiomementioning
confidence: 99%